Management of primary thoracic neuroblastic tumors in children: An observational study - Vivek Shanmugam; N Karpaga Vinayagam; R Senthilnathan (Wolters Kluwer Medknow Publications, 2022)
Aims: The mediastinum is the second common site of origin of pediatric neuroblastic tumors. Primary thoracic neuroblastoma (NB) is considered to be a site with favorable outcome and is reported to have a better prognosis than the other sites of origin. This is an observational study on our experience in the management of children with primary thoracic neuroblastic tumors. Materials and Methods: A retrospective observational review of the medical records of all the children treated for primary thoracic neuroblastic tumors including NB, ganglioneuroblastoma, and ganglioneuroma over a period of 8 years from January 2011 to December 2018 at our Institute was performed. We analyzed the factors including age, stage, histology, symptoms at presentation, surgical management, adjuvant treatment, and the 2-year survival of patients. Results: A total of 23 cases of primary thoracic neuroblastic tumors were identified during the study period. Ten patients had Stage III disease (43%), six had Stage IV (26%), four had Stage II, and three patients had Stage I. A total of four children (17%) died during the study period. A total of 13 children underwent complete excision of the tumor. Conclusion: In this retrospective review, we have observed that the mediastinal site of origin alone did not uniformly confer an excellent prognosis for all the patients. While the patients with lower stage tumors, favorable biological profile, and infants had excellent prognosis, in another small subset of patients with undifferentiated histology, the prognosis was guarded with an increased risk of recurrence. The clinical presentation with pleural effusion and compression of the airway at the time of presentation was associated with poor outcome.